2018
DOI: 10.1186/s13018-018-0798-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation and arthroscopic treatment of symptomatic posterior cruciate ligament cyst

Abstract: BackgroundGanglion cyst of cruciate ligaments is a rare lesion; the prevalence is 0.3–0.8%. The purpose of this study was to present clinical features of symptomatic posterior cruciate ligament (PCL) cyst, introduce the arthroscopic excision technique, and evaluate the clinical outcome.MethodsA series of 11 patients with symptomatic PCL cyst from November 2012 to December 2014 were involved in this retrospective study. Detailed medical history collecting and physical examination were conducted. Magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Their etiology is still unclear, but they seem to be associated mostly with trauma or chronic injuries. 1,4 The main symptom of PCL cysts is knee pain during flexion. MRI is the gold standard to detect and accurately locate cysts associated with cruciate ligaments in the knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their etiology is still unclear, but they seem to be associated mostly with trauma or chronic injuries. 1,4 The main symptom of PCL cysts is knee pain during flexion. MRI is the gold standard to detect and accurately locate cysts associated with cruciate ligaments in the knee.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that the cyst walls are not removed with these procedures, leading to a potentially higher risk of recurrence. 1,3,6 The cyst walls can be removed completely using an arthroscopic procedure, although this is technically challenging to perform using anterior portals only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those lesions are mainly diagnosed in patients aged between 20 and 40 years [ 3 , 5 , 6 ], and a male preponderance has been reported [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ganglion cysts (GC) are benign tumor-like lesions usually going out from mucinous degeneration of collagenous structures [1,2]. They could occur in several anatomic areas but GC arising from cruciate ligaments are rare [3,4] with a prevalence of 0.36% or 0.8% respectively when diagnosed by magnetic resonance (MR) or by arthroscopy [3,[5][6] However other studies of GC prevalence refer ranges from 0.2% to 1.9% [7][8][9], with posterior cruciate ligament ganglion cysts (PCLGC) being five times less frequent than those identify in anterior cruciate ligament [5,10]. This lesion is mainly diagnosed in people aged 20-40 years-old and a male predominance has been reported [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%